Paradoxes and wonders of intrinsic disorder: Complexity of simplicity. Issue 1 (1st January 2016) - Uversky, Vladimir N.
ABSTRACT: At first glance it may seem that intrinsically disordered proteins (IDPs) and IDP regions (IDPRs) are simpler than ordered proteins and domains on multiple levels. However, such multilevel simplicity equips these proteins with the ability to have very complex behavior.